Nutrition for elderly individuals during the Covid-19 pandemic - Purwita Wijaya Laksmi (Indonesian Nutrition Association, 2022)
Aging process, genetic factor, lifestyle, and disease(s) give contribution to the phenotype of robust, prefrail or frail elderly. The frailer the elderly, the more vulnerable they become to poor health outcomes. Aged patients are more likely to have adverse outcomes from Coronavirus disease-19 (COVID-19). Recovery from such disease also take a longer time compared to the younger age group